2021
DOI: 10.3390/jcm10122689
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Multiple Sclerosis—A Multifaceted Association

Abstract: Background: Given the common elements in the pathophysiological theories that try to explain the appearance and evolution of obesity and multiple sclerosis, the association between the two pathologies has become an increasingly researched topic in recent years. On the one hand, there is the chronic demyelinating inflammation caused by the autoimmune cascade of multiple sclerosis, while on the other hand, according to the latest research, it has been shown that obesity shares an inflammatory component with most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 78 publications
1
25
0
1
Order By: Relevance
“…Interestingly, there is a multifaceted association between obesity and MS. High body mass index (BMI) genetic variants in adolescent and adult patients are associated with the onset of MS [58,59]. Autoimmune diseases are usually associated with polymorphisms of the genes that regulate the function of the immune system; in this context, the HLA antigen D-related β1 subunit (DRB1) gene (HLA DRB1*15:01), within the major histocompatibility complex, has been identified as the primary locus associated with this correlation [58,60]. Furthermore, obesity is also correlated with the development of MS due to the polymorphisms found in fat mass obesity (FTO)-related genes [61,62].…”
Section: Genetic Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there is a multifaceted association between obesity and MS. High body mass index (BMI) genetic variants in adolescent and adult patients are associated with the onset of MS [58,59]. Autoimmune diseases are usually associated with polymorphisms of the genes that regulate the function of the immune system; in this context, the HLA antigen D-related β1 subunit (DRB1) gene (HLA DRB1*15:01), within the major histocompatibility complex, has been identified as the primary locus associated with this correlation [58,60]. Furthermore, obesity is also correlated with the development of MS due to the polymorphisms found in fat mass obesity (FTO)-related genes [61,62].…”
Section: Genetic Susceptibilitymentioning
confidence: 99%
“…The FTO rs9939609 polymorphism has consistently been associated with a higher BMI across different populations, including the Kuwaiti population [63]. Another link between MS and obesity is the adipokine's capacity to modulate the immune system by increasing pro-inflammatory response [58,59]. It is still necessary to deeply understand how these risk genetic variants are regulated and the pathways in which they are involved in the immune system of these patients [54].…”
Section: Genetic Susceptibilitymentioning
confidence: 99%
“…Obesity is one of the major conditions that gives rise to a myriad of comorbid, inflammation driven, chronic diseases particularly as aging progresses [ 62 , 63 ]. Table 2 illustrates examples of 43 comorbid NCDs for obesity [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. The obese population carries one of the highest risks for multiple future NCDs of any disease-burdened cohort.…”
Section: Two High-impact Examples Of Ncdsmentioning
confidence: 99%
“…It is well known that HFD contributes to systemic low-grade inflammation in the body (Duan et al, 2018). Furthermore, many studies reported that HFD-induced inflammation can exacerbate the progression of autoimmune diseases, such as multiple sclerosis (Schreiner and Genes, 2021), systemic lupus erythematosus (SLE; Hanna Kazazian et al, 2019), and rheumatoid arthritis (RA; Poudel et al, 2020). However, there are few studies elucidating the relationship between HFD and pSS.…”
Section: Introductionmentioning
confidence: 99%